PERKEMBANGAN RUANG SOSIAL DAN RELIGIUS DI KOTA METRO TAHUN 2000 - 2017 - Dian Rizki Dayanti; Sumiyatun Sumiyatun (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
The presence of social and religious space in a city can be one of the choices for people to eliminate fatigue that is felt so that the community is able to interact, socialize, gather and create in an emotional (communal) building besides that it can support and direct the community towards progress in religious as well as the noble values of their ancestors so that the presence of social public space and religious public space in a city is very important for the community. The approach used in this study is a qualitative method with a type of naturalistic research. Data analysis techniques that will be used are data reduction, data presentation and conclusion drawing. Based on the results of the study, it was found that the development of social space and religious space in Metro City experienced a rapid increase. This is evidenced by the conduct of renovations carried out in social and religious spaces in Metro City which can have a positive impact on the economy of the community. The conclusion of this study is the development of social space and religious space so that in social space not only as a place for recreation but can support the economy of society in addition to the religious space not only as a place for worship but can also be used as an Islamic nuance recreation.